Effect of scanning speed on laser joining of carbon fiber reinforced PEEK to titanium alloy. (September 2020) - Tan, Caiwang; Su, Jianhui; Zhu, Baohua; Li, Xiaoting; Wu, Laijun; Chen, Bo; Song, Xiaoguo; Feng, Jicai
Highlights: CTi0.42 V1.58 phase was observed and confirmed at the interface. Dynamic behavior during laser joining CFRP/Ti was captured. Finding importance of the bonding width of the resin and fiber-resin mixture. Numerical simulation model accurately predicted the trend of joining strength. Abstract: Laser lap joining of carbon fiber reinforced plastics (CFRP) to titanium (Ti) alloy using various scanning speed was performed and the influence of scanning speed on joining process was investigated. The high speed camera was adopted to visualize the joining process and defects. The tensile-shear force was tested and the fracture surface was observed by optical microscope. Besides, the numerical simulation of temperature field was conducted to reveal the joining mechanism. The results indicated that fewer defects on titanium alloy surface and less bubbles inside CFRP were obtained with the experimental condition of higher scanning speed. Both mechanical interlocking and chemical bonding occurred at the interface. The compound layer was generated and was confirmed as CTi0.42 V1.58 phase because of the carburization of titanium alloy. The thickness of compound layer increased with the decrease of scanning speed. Tensile-shear force first increased and then decreased as the travelling speed increased. When the travelling speed was 0.8 m/min, maximum tensile-shear force of 1024 N was obtained. The bonding width of the resin, and bonding ratio of the mixture of carbon fibers and resin also reached the maximum value at this experimental condition. This behavior was verified by results of temperature field simulation that the melting temperature range of CFRP first increased and then declined as the scanning speed increased. The fluctuation of the tensile-shear force of the CFRP/Ti joint was also explained by the developed simulation model.